The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1590/s1415-43662013000500009
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia e propriedades físicas de solo segundo sistemas de manejo em culturas anuais

Abstract: RESUMOQualidade física do solo é sua capacidade de sustentar o pleno desenvolvimento das plantas. O objetivo deste trabalho foi estudar diferentes sistemas de semeadura direta para a produção de grãos em áreas de agricultura familiar sob Latossolo Vermelho no norte do Paraná, Brasil, através do estudo da morfologia e de algumas propriedades físicas do solo. O estudo foi baseado na descrição da estrutura de solo de perfis culturais em áreas cultivadas com lavouras anuais sob diferentes sistemas de manejo de sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
2
4
0
1
Order By: Relevance
“…As hydraulic conductivity (intensity property) is a property that depends on bulk density and soil porosity (capacity properties), these properties have been determined and have shown that the Fma/gtΔμ (perennial pasture) and Lma/gtΔμ (sugarcane) structures differ from the CΔ and Cµ structures, both for density and for porosity (TP, Ma, and Mi) under the two land uses, which is in agreement with Tavares Filho et al (1999), Silva et al (2000), Folegatti et al (2001), Neves et al (2003), Llanillo et al (2006), Portella et al (2012), and Fuentes- Llanillo et al (2013). This indicates that field description prior to sampling to determine the capability properties (soil density and porosity) is very important for interpreting the data when we want to assess the physical state to diagnose and quantify the changes imposed by environmental and anthropogenic factors on the internal structure of the soil and on its functional properties or processes with respect to plant development (Fuentes-Llanillo et al, 2013). ).…”
Section: Soil Profilesupporting
confidence: 56%
See 4 more Smart Citations
“…As hydraulic conductivity (intensity property) is a property that depends on bulk density and soil porosity (capacity properties), these properties have been determined and have shown that the Fma/gtΔμ (perennial pasture) and Lma/gtΔμ (sugarcane) structures differ from the CΔ and Cµ structures, both for density and for porosity (TP, Ma, and Mi) under the two land uses, which is in agreement with Tavares Filho et al (1999), Silva et al (2000), Folegatti et al (2001), Neves et al (2003), Llanillo et al (2006), Portella et al (2012), and Fuentes- Llanillo et al (2013). This indicates that field description prior to sampling to determine the capability properties (soil density and porosity) is very important for interpreting the data when we want to assess the physical state to diagnose and quantify the changes imposed by environmental and anthropogenic factors on the internal structure of the soil and on its functional properties or processes with respect to plant development (Fuentes-Llanillo et al, 2013). ).…”
Section: Soil Profilesupporting
confidence: 56%
“…Grass root may increase the amount of soil organic matter and biological activity, and that may improve the quality of the soil structure (Horn and Peth, 2009;Mentges et al, 2016;Reichert et al, 2016). However, Tavares Filho et al (1999), Portella et al (2012), Fuentes-Llanillo et al (2013), and Silva et al (2014) reported that the presence of these Dμ internal states indicates a non-critical drop in macroporosity (caused by the onset of compaction). Furthermore, these authors state that the Dμ internal state would continue to evolve into D units if this kind of soil usage continued.…”
Section: Soil Profilementioning
confidence: 99%
See 3 more Smart Citations